Chemical Synthesis and Antipseudomonal Activity of Al-Doped NiO Nanoparticles - Irum, Sidra; Andleeb, Saadia; Sardar, Sumbal; Mustafa, Zeeshan; Ghaffar, Ghazanfar; Mumtaz, M.; Mubasher,; Arslan, Muhammad; Abbas, Mudassar (Frontiers in Materials, 2021)
Synthesis of efficient antibacterial agents has become extremely important due to the emergence of antibiotic resistant bacteria. This is especially true for Pseudomonas aeruginosa, an opportunistic pathogen having ability to rapidly develop resistance to multiple classes of antibiotics thus limiting the efficacy of antibiotics approved for clinical use. Aluminum (Al)-doped NiO nanoparticles are of special interest due to their enhanced antipseudomonal properties at certain Al-doping levels. The composite hydroxide mediated (CHM) approach was opted for the synthesis of pure nickel oxide (NiO) and Al-doped nickel oxide (Ni1-xAlxO; x = 5, 10, 15, 20, 25 and 30 wt. %) nanoparticles. X-ray diffraction (XRD) technique was used for structural analysis of these nanoparticles. Morphology and elemental composition of these nanoparticles were investigated by scanning electron microscopy (SEM) and energy dispersive X-ray (EDX) spectroscopy, respectively. The optical properties were investigated by using UV-visible spectroscopy and Kubelka-Munk Theory and Tauc relation were employed for energy bandgap calculation of these nanoparticles. The antibacterial activity of representative Al-doped NiO nanoparticles was assessed on multidrug-resistant clinical P. aeruginosa strains. The agar well and disc-diffusion methods were used to assess the antibacterial efficacy of (Al)-doped NiO compared to pure NiO nanoparticles. Interestingly, a gradual increase in the antibacterial activity was observed with increasing Al-doping concentration and the highest antibacterial activity was observed at x =15 wt. % Al-doping concentration. The antipseudomonal efficacy of Ni1-xAlxO nanoparticles was comparable to aztreonam antibiotic, primarily used for Gram-negative bacterial infections. Hence, it is proposed that these nanoparticles can be used for coating surgical devices, bone prostheses, medical implants, antibacterial clothing and in pharmaceutical formulations as burn ointments to produce the antimicrobial effect.